2007
DOI: 10.5897/ajb2007.000-2380
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and gill net selectivity of Pellonula leonensis in the Lower Nun River, Niger Delta, Nigeria

Abstract: The abundance of Pellonula leonensis in relation to location, photoperiod, depth, tide, season and gill net selectivity was studied from May 2001 to April, 2002 in the Lower Nun River, Niger Delta. Three sets of gill net with stretched mesh sizes of 8, 12 and 15 mm respectively were used each measuring 35 m in length and 3 m in depth having a surface area of 105 m 2. Abundance was least in September and highest in February and P. leonensis was more dominant in the convex area of the river and lowest in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…While relative fecundity was determined as the proportion of absolute fecundity to the eviscerated body weight (number of mature eggs per gram of the body weight) (Kingdom & Allison, ).…”
Section: Methodsmentioning
confidence: 99%
“…While relative fecundity was determined as the proportion of absolute fecundity to the eviscerated body weight (number of mature eggs per gram of the body weight) (Kingdom & Allison, ).…”
Section: Methodsmentioning
confidence: 99%
“…Evidences exist that in the Lagos lagoon, gill net is the dominant fishing gear used in the water body (Kingdom and Allison, 2007). Emmanuel et al (2008) observed size selection of gill nets as being crucial to fisheries management to maximize sustainable yields.…”
Section: Introductionmentioning
confidence: 99%